Fetal hemoglobin Bart’s hydrops fetalis: pathophysiology, prenatal diagnosis and possibility of intrauterine treatment - Phudit Jatavan (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. This review aimed at comprehensively summarizing current available reports regarding the ultrasound markers and biomarkers in predicting fetal Hb Bart’s disease and evaluate the potential role of cardiac function assessment in a clinical practice. This review involves various methods in prenatal predicting fetal Hb Bart’s disease or alpha-thalassemia major and attempts to provide valuable insights regarding the underlying mechanisms responsible for heart failure in Hb Bart’s fetuses. Moreover, this information may be used to predict the cardiac function before the development of hydrops fetalis. Finally, the affected Hb Bart’s fetus could be the best model of the study on cardiovascular response to fetal anemia, thus the cardiovascular ultrasound and molecular assessment may be helpful in predicting the prognosis or in making a choice in the management of the fetal anemia condition. In conclusion, ultrasound findings especially cardiomegaly and an increase in peak systolic velocity of the middle cerebral artery (MCA-PSV) are helpful in predicting the future hydrops fetalis and ultrasound assessment of fetal cardiac function is potentially helpful in clinical practice. Finally, this review highlights the pathogenesis of hydropic changes secondary to fetal anemia.